Leadership Behaviors of School Administrators Affecting Academic Administration in Educational Institution under the Nakhonpathom Primary Educational Service Area Office 2 - Netkobkuea, Chonnisa (Journal of Dhamma for Life, 2024)
This thesis has a purpose 1) To study the leadership behavior of educational institution administrators under the Nakhon Pathom Primary Educational Service Area Office, Area 2. 2) To study academic administration in educational institutions. Under the the Nakhon Pathom Primary Educational Service Area Office, Area 2 3) Leadership behaviors that affect academic administration in educational institutions Studying under the Nakhon Pathom Primary Educational Service Area Office, Area 2 Sample group in this research Schools under the jurisdiction of the Nakhon Pathom Primary Educational Service Area Office, Area 2, 92 schools, number of informants: 276 people, consisting of school directors/deputy school directors Head of Academic Administration and teachers in educational institutions under the Nakhon Pathom Primary Educational Service Area Office, Area 2. The research instrument was a questionnaire. Data were analyzed using ready-made programs. Statistics used in data analysis include frequency (Frequency), percentage (Percentage), mean (Arithmetic Mean), standard deviation (Standard Deviation), hypothesis testing. Stepwise multiple regression analysis was used. The results of research were found that: Analysis of the leadership behavior of school administrators under the Nakhon Pathom Primary Educational Service Area Office, Area 2, overall at the highest level. When considering each aspect, it was found that it was at the highest level in every aspect. Arranged from highest to lowest as follows: Persuasion initiative Being able to socialize well good coordination assistance Knowing how to improve and respect, respectively. Analysis of the results of academic administration in educational institutions under the Nakhon Pathom Primary Educational Service Area Office, Area 2, overall at the highest level. When considering each aspect, it is at the highest level in every aspect. Arranged from highest to lowest as follows: educational supervision Followed by measurement, evaluation, and transfer of academic results. And the aspect ranked last is the development of a quality assurance system. 3. Leadership behavior of administrators that affects administration in educational institutions. Under the the Nakhon Pathom Primary Educational Service Area Office, Area 2, including leadership behavior in helping (X4), being able to socialize well (X7), knowing how to improve (X2), having initiative (X1), giving acceptance. Respect (X3) affects academic administration Under the Nakhon Pathom Primary Educational Service Area Office, Area 2 as a whole (Ytot) with statistical significance at the .01 level. Forecasting equation in raw score form " Ŷtot” = 2.873 + .142 (X4) + -.125 (X7) + .188 (X2) + .119 (X1) + .119 (X3) Forecasting equation in standard score form Z^' = .019 (X4) + .019 (X7) + .021 (X2) + .018 (X1) + .018 (X3)